Late middle Eocene epoch of Libya yields earliest known radiation of African anthropoids. - (:unkn) unknown (My University, 2010)
Reconstructing the early evolutionary history of anthropoid primates is hindered by a lack of consensus on both the timing and biogeography of anthropoid origins. Some prefer an ancient (Cretaceous) origin for anthropoids in Africa or some other Gondwanan landmass, whereas others advocate a more recent (early Cenozoic) origin for anthropoids in Asia, with subsequent dispersal of one or more early anthropoid taxa to Africa. The oldest undoubted African anthropoid primates described so far are three species of the parapithecid Biretia from the late middle Eocene Bir El Ater locality of Algeria and the late Eocene BQ-2 site in the Fayum region of northern Egypt. Here we report the discovery of the oldest known diverse assemblage of African anthropoids from the late middle Eocene Dur At-Talah escarpment in central Libya. The primate assemblage from Dur At-Talah includes diminutive species pertaining to three higher-level anthropoid clades (Afrotarsiidae, Parapithecidae and Oligopithecidae) as well as a small species of the early strepsirhine primate Karanisia. The high taxonomic diversity of anthropoids at Dur At-Talah indicates either a much longer interval of anthropoid evolution in Africa than is currently documented in the fossil record or the nearly synchronous colonization of Africa by multiple anthropoid clades at some time during the middle Eocene epoch.
Keywords: African Research